Corporate social responsibility practices among the SMEs in Malaysia – a preliminary analysis / Norhafizah Norbit, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin. - Norbit, Norhafizah; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Universiti Teknologi MARA Cawangan Selangor, 2017)
There are four main objectives of this study. First, to examine the level of Corporate Social Responsibility (CSR) practices in selected Malaysian small and medium enterprises (SMEs). Second, to determine the motivation for implementing CSR practices. Third, to determine the barriers to the implementation of CSR practices. Finally, to examine the attitude of twenty selected Malaysian SMEs owners towards CSR practices. This study employed a mixed method in data collection and analysis via survey questionnaires to the selected SMEs and archival analysis by examining the financial reports of those SMEs. This study found that SMEs is still lag behind in implementing CSR practices. Although they understand the benefits such as enhancing company’s reputation and promote brand name, limited funds available and proper training required prevented them from implementing effective CSR practices. This study also found that the SMEs’ owners have a positive attitude towards CSR practices.